Influence of Online Learning Platforms on the Implementation of Adult Education Programs in Borno State - Istifanus, Barka; Inusa , Diana; Adamu , Fatima (Kashere Journal of Education, 2025)
The study sought to investigate the effects of online learning platforms on the implementation of adult education programmes and to explore strategies that educators can use to optimise these platforms to meet the needs of adult learners. To guide the research, three research questions and three objectives were formulated. A descriptive survey research design was employed, with the study population consisting of 127 adult educators randomly selected from Adult Education Learning Centers in Borno State, Nigeria. Given the manageable population size, no sampling was required, allowing the researchers to gather comprehensive data without significant challenges or errors. Data were collected using a structured questionnaire developed by the researchers, titled the “Technology for Adult Education Programme Questionnaire (TAEPQ)", which was face-validated by three experts, including two from the Department of Adult Education and Extra-Mural Studies at the Borno State Agency for Mass Education. The reliability of the instrument was confirmed using Cronbach’s Alpha, yielding a high coefficient of 0.82. Data analysis was conducted using mean and standard deviation. The findings indicate that online learning platforms can significantly enhance access to adult education and boost learner engagement. However, effective implementation requires careful attention to learner needs, instructional design, and technical support. The study further revealed that educators can optimise online learning by incorporating interactive and collaborative activities, offering personalised feedback and support, and adopting a learner-centred approach that addresses the individual goals and needs of adult learners. Based on these findings, the study recommended that adult educators and policymakers take steps to improve the quality of online learning to ensure that learners have a positive and productive educational experience.